2020
DOI: 10.3389/fpsyt.2020.00661
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortical Functional Networks in Patients With Schizophrenia and Bipolar Disorder: A Resting-State Electroencephalographic Study

Abstract: Background: Pathologies of schizophrenia and bipolar disorder have been poorly understood. Brain network analysis could help understand brain mechanisms of schizophrenia and bipolar disorder. This study investigates the source-level brain cortical networks using resting-state electroencephalography (EEG) in patients with schizophrenia and bipolar disorder. Methods: Resting-state EEG was measured in 38 patients with schizophrenia, 34 patients with bipolar disorder type I, and 30 healthy controls. Graph theory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
(140 reference statements)
2
16
0
Order By: Relevance
“…Kim et al 34 showed decreased CC and e ciency, and increased PL in the alpha band during resting-state EEG in patients with BD. Another resting-state EEG study demonstrated that BD showed higher strength and CC, and lower PL in the theta band 35 . Furthermore, several neuroimaging studies have shown altered functional brain networks in MDD patients.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Kim et al 34 showed decreased CC and e ciency, and increased PL in the alpha band during resting-state EEG in patients with BD. Another resting-state EEG study demonstrated that BD showed higher strength and CC, and lower PL in the theta band 35 . Furthermore, several neuroimaging studies have shown altered functional brain networks in MDD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Effect sizes were computed based on the partial eta squared (η 2 ). The procedure for the statistical analysis followed our previous study 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations